Ethno-cultural Night Festival "Open Your Heart to the World!" in Multicultural Education of Students - Natalia A. Kornilova; Yana G. Semenova; Svetlana N. Fedorova (Развитие образования, 2022)
The purpose of the article is to describe the experience of Night Fest «Open your heart to the world» at Mari State University. Representatives from 35 countries of the world study here: Azerbaijan, Afghanistan, India, Comoros, Kyrgyzstan, Korea, Kyrgyzstan, Sudan, Tatarstan, Tajikistan, Turkmenistan, Turkey, Uzbekistan, Ukraine and others. Therefore, the university pays much attention to use various methods and forms of work in multicultural education of students. Research material. The main source of research is the experience of conducting ethno-cultural festival with students of different countries in the Federal State Budgetary Educational Institution of Higher Education «Mari State University. The results of the research and their discussion: the specifics of organizing the festival Night Fest of national cultures «Open your heart to the world» on the basis of FSBEI of HE «Mari State University» are analyzed, the step-by-step organization of the festival with reflection of separate components of national cultures (national games, national costume, national song, national dance and national dish) is presented, the conclusions are made about the importance of national culture, customs and traditions of the people in revealing the talents of students in building a single space of personal development through various activities that contribute to the assimilation of knowledge about the peculiarities of different cultures, different behavioral norms, the ability to build relationships with representatives of other cultures.